Analysis of the impact of Praganna Irrigation Project (PIP) on income and employment in Dang District of Nepal - Pradhyoti, Yadav; Dutta, Jay Prakash; Regmi, Punya Prasad; Chaudhary, Narendra Kumar (Journal of Agriculture and Environment, 2015)
A survey research was conducted to assess the performance of Praganna Irrigation Project with respect to farm income and employment in Dang district of Nepal. Simple random sampling was used to select 60 beneficiaries and 30 non-beneficiaries as sampling units to comprise a sample size of 90. Representatives of WUGs and officials of PIP were interviewed through checklists. Altogether there were 75 WUGs, which are responsible for distribution of irrigation water equitably and collection of irrigation charges effectively. A comparative study was made between the beneficiaries and nonbeneficiaries under PIP. The total farm assets of beneficiaries were estimated at NRs. 1,150,975 and differed significantly with the non-beneficiaries with total farm assets of NRs. 875,185. A significant difference was observed between on farm income of beneficiaries (NRs.183,260) and non– beneficiaries (NRs. 31,453). The net farm income of the beneficiaries and non-beneficiaries were estimated at NRs. 79,993 and NRs. 13,077 respectively and the difference were significant among the categories of respondents. The total farm income was significantly affected by landholding, total variable cost, cropping intensity, and employment in case of beneficiaries whereas only employment significantly affected total farm income in case of non-beneficiaries. Gini coefficients for gross household and gross farm income were calculated at 0.37 and 0.44 respectively for beneficiaries and 0.44 and 0.27 respectively for non-beneficiaries. So, there existed inequality in distribution of gross household and gross farm incomes within both categories. The study also indicated the huge potentiality of PIP for increasing farm income in the command area of PIP.